New insights into the effects of biomaterial chemistry and topography on the morphology of kidney epithelial cells. (20th June 2017) - Hulshof, Frits; Schophuizen, Carolien; Mihajlovic, Milos; van Blitterswijk, Clemens; Masereeuw, Rosalinde; de Boer, Jan; Stamatialis, Dimitrios
Abstract: Increasing incidence of renal pathology in the western world calls for innovative research for the development of cell‐based therapies such as a bioartificial kidney (BAK) device. To fulfil the multitude of kidney functions, the core component of the BAK is a living membrane consisting of a tight kidney cell monolayer with preserved functional organic ion transporters cultured on a polymeric membrane surface. This membrane, on one side, is in contact with blood and therefore should have excellent blood compatibility, whereas the other side should facilitate functional monolayer formation. This work investigated the effect of membrane chemistry and surface topography on kidney epithelial cells to improve the formation of a functional monolayer. To achieve this, microtopographies were fabricated with high resolution and reproducibility on polystyrene films and on polyethersulfone‐polyvinyl pyrrolidone (PES‐PVP) porous membranes. A conditionally immortalized proximal tubule epithelial cell line (ciPTEC) was cultured on both, and subsequently, the cell morphology and monolayer formation were assessed. Our results showed that L‐dopamine coating of the PES‐PVP was sufficient to support ciPTEC monolayer formation. The polystyrene topographies with large features were able to align the cells in various patterns without significantly disruption of monolayer formation; however, the PES‐PVP topographies with large features disrupted the monolayer. In contrast, the PES‐PVP membranes with small features and with large spacing supported well the ciPTEC monolayer formation. In addition, the topographical PES‐PVP membranes were compatible as a substrate membrane to measure organic cation transporter activity in Transwell® systems. Copyright © 2016 John Wiley & Sons, Ltd.